Liturgi Berwajah Pastoral sebagai Ruang Pemulihan Spiritual Jemaat GPM Kariu Pascakonflik Komunal - Salenussa, Peter Boris; Ruimassa, Aleta; Nanuru, Ricardo (Jurnal Ilmiah Religiosity Entity Humanity (JIREH), 2025)
The purpose of this study is to formulate a pastoral liturgy model that functions as a space for spiritual healing and social reconciliation for the Kariu congregation of the Maluku Protestant Church (GPM) after communal conflict on Haruku Island. The method used is a qualitative approach with Richard Osmer's practical theology paradigm, through four theological tasks, namely descriptive-empirical, interpretive, normative, and pragmatic. Data were collected through observation, in-depth interviews, Focus Group Discussions (FGD), and documentation studies. The results of the study show that routine worship practices do not fully address the social, psychological, and spiritual recovery needs of the congregation after the conflict. The congregation needs a liturgy that provides space for lamentation, prayers for healing, strengthening of faith, and integration of post-conflict life experiences and local culture. The conclusion of this study is that pastoral liturgy needs to be understood and designed as a means of contextual and transformative pastoral care. Liturgy does not only function as a formal ritual, but as a medium for spiritual healing and social reconciliation of post-conflict congregations.